Impact of obesity in colorectal endoscopic submucosal dissection: single-center retrospective cohort study - Jun Tachikawa (BMC Gastroenterology, 2021)
Abstract Background When performing colorectal endoscopic submucosal dissection (ESD) in obese patients, technically difficult cases are sometimes experienced because of difficulty with the insertion of the colonoscope, poor scope maneuverability, or an abundance of fat tissue in the submucosal layer. Since the association between obesity and colorectal ESD has not been investigated, we evaluated the clinical impact of obesity in patients who underwent colorectal ESD. Methods We retrospectively reviewed 535 patients who underwent colorectal ESD between April 2012 and February 2019. Patients were divided into three groups based on their body mass index (BMI): a control group (BMI < 25 kg/m2), an overweight group (25 kg/m2 ≤ BMI < 30 kg/m2), and an obese group (BMI ≥ 30 kg/m2), and the short-term clinical outcomes were analyzed to assess the safety and difficulty of colorectal ESD. Results No significant difference in the procedure times, en bloc resection rates, pathological diagnoses, or complications were seen among the groups. While the amount of sedative per body weight was significantly lower in the group with a higher BMI (flunitrazepam: 1.75 × 10−2 [1.27 × 10−2–2.34 × 10−2] mg/kg vs. 1.48 × 10−2 [1.08 × 10−2–2.03 × 10−2] mg/kg vs. 1.16 × 10−2 [0.98 × 10−2–1.54 × 10−2] mg/kg, P < 0.001; pethidine: 0.63 [0.55–0.72] mg/kg vs. 0.50 [0.46–0.56] mg/kg vs. 0.39 [0.32–0.45] mg/kg, P < 0.001), a reduction in percutaneous arterial oxygen saturation occurred significantly more frequently in the group with a higher BMI (123 [30.2%] vs. 43 [43.9%] vs. 10 [55.6%], P = 0.005). When the procedures were performed by trainees, the number of cases that required a procedure time of longer than 90 min was significantly larger in the group with a higher BMI (27 [10.8%] vs. 14 [21.9%] vs. 3 [25.0%], P = 0.033). Conclusions This study showed that colorectal ESD could be performed safely and effectively in obese patients. However, ESD in obese patients requires attention, particularly to changes in respiratory conditions.